Roman law in Spain prior to the Lex Wisigothorum - Kofanov, Leonid (SCHOLE, 2010)
In this analytical outline of the history of roman law in Spain from the 2nd c. B. C. E. to the 6th c. C. E., the author notices that even in the 2nd century B. C. E. Roman legal and political institutes exercised so great influence on the Republican’s allies in Spain, that the emerging provincial government adopted almost all their characteristic elements, including the majority of public regulations, legal proceedings, and language. Narrative and epigraphic evidences leave no doubt that already by the beginning of the Common Era the municipal law in Spain had effectively copied and assimilated all public and private Roman legal institutes. The most active involvement of the Spanish in Roman politics (including the Roman emperors descending from this region) made the province an important propagator of Roman legal and political tradition to the rest of the western world, whilst the consequent assimilation of the Goths (Roman allies for more that a century) helped Spain to become the last outpost of roman law in Europe until the Arabian invasion, and the Breviarium of Alaric is a good evidence to this process.